THE MEASURING WORM OF THE PANOJA Pleuroprucha asthenaria, PLAGUE OF THE SORGE - PULIDO-F., JAIME (Revista Colombiana de Entomología, 1979)
Insects attacking sorghum plants during the flowering and grain filling stages have been increasing lately in number and incidence, nevertheless, very little research has been done in Colombia. The measuring worm, Pleuroprucha asthenaria Walker (Lepidoptera: Geometridae) of sorghum head was found in the Cauca Valley attacking the sorghum plant by as much as 20 larvae per plant during 1979 - 1980 season. It was necessary to use chemical control to reduce the insect attack. A biological study of the insect, at 23,6°C and 73% R.H. average, has shown the longevity for an egg, larvae, prepupa, and pupa stages of 3,4; 12,3; 0,5 and 7,2 days, respectively. The adult female had longevity of 4 to 26 days, and the male, 4 to 17 days. The rYreoviposition period lasted 4,8 days on average. The highest oviposition took place between the Sth and the 20th day of the female life. A single female laid 111 eggs per day and 586 eggs for a complete period of 17 days. Eggs were laid mainly on the glumes of sorghum heads it was observed sexual dimorphism in the antena of the adults was described. The younger larvae had preferences for the fresh soft tissue of flowering structures, and the older ones (last three instars) preferred grain in the milk stage. A larva may consume more than three grains. Oedicephalus sp. (Hymenoptera: Ichneumonidae) was found as a parasite of pupae. Orius tristicolor Herring (I-Iemiptera: Anthocorldae) was detected as main natural control, attacking eggs, and young and intermediate larvae of the pest. A good level of parasitism by Trichogramma pretiosum Riley, was detected in laboratory conditions; this parasite was obtained from Diatraea saccharalis Fabricius under laboratory conditions.